Metabolic components of cattle: water-soluble tracers for determining water turnover and partitioning by cattle, Pawnee site - Bement, B. E., author; Knox, K. L., author; Hyder, D. N., author; Natural Resource Ecology Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1969)
The objective of the project on water soluble tracers for determining water turnover and partitioning by cattle is to determine the energy and nutrient components associated with the water components consumed and excreted by cattle. For example, if fecal water output can be determined, the dry matter and energy concentrations can be added to arrive at total daily amounts.
Keywords: polyethylene glycol-14C study; gastro-intestinal tract water tracers; water partitioning; Pawnee National Grasslands; Central Plains Experimental Range; Grassland ecology; Water; Cattle